How has the Covid-19 Pandemic Affected Incomes And Euro Perceptions In Romania: Array - Floroiu, Otilia Georgiana (Journal of Danubian Studies and Research, 2020)
These are times of uncertainty and fear. The pandemic effects will be felt for a long time and will bring changes to the social, economic and political sphere. The European Union is trying to adopt measures in order to protect its member states, encourage economic cooperation and boost trust in the European mission. Even so, the Eurozone will still face significant challenges. We are interested in finding out if Romanians’ confidence in the Euro currency has been affected by this pandemic. High levels of confidence are a key ingredient for a healthy economy and the success of the euro adoption also depends on people’s perception of the transition process. In order to assess this matter, we have addressed some of the Eurobarometer questions to 1000 people from Romania and compared the results to the survey conducted in 2019. As attitude towards the future is influenced by income fluctuation, we have also considered analyzing the impact of the pandemic on the household income and expenditure to be important.